Successful Treatment of Left Ventricular Perforation Occurring After Insertion of an Impella Device - Glazier, James J.; Kaki, Amir; Baciewicz, Frank (International Journal of Angiology, 2018)
The Impella device is a miniaturized ventricular assist device that is being increasingly used to increase the safety and efficacy of high-risk coronary interventions and to treat patients with acute myocardial infarction complicated by cardiogenic shock. The device has a miniaturized rotary pump mounted on a 9F catheter with a pigtail conformation. The pump draws blood from the left ventricular cavity and expels it into the ascending aorta and systemic circulation. We report a patient who, following insertion of an Impella device, developed angiographically documented left ventricular perforation with marked hemodynamic instability. Our successful management of this patient is described and potential mechanisms responsible for the perforation are discussed.
Keywords: left ventricular perforation; impella device; ventricular assist device; cardiac surgery; high risk coronary intervention; tamponade; complication